Exploring the Perceptions of ICT Use in Higher Education: An Empirical Study from Bangladesh - Das, Rajib Chandra; Hashmi, Nushrat; Sultana, Zakia (Transpublika Publisher, 2025)
Information and communication technologies (ICTs) exert a substantial influence on enhancing students’ academic competencies in Bangladesh. The primary aim of this inquiry is to ascertain undergraduate learners’ viewpoints regarding the deployment of ICT in their studies. In addition, the investigation explores the hindrances that may obstruct the optimal integration of ICT within higher education from the students’ perspective. A survey-based methodology was employed, adopting a quantitative orientation. The study utilized both primary and secondary sources of evidence. For the primary data, an online questionnaire was disseminated to undergraduate students of CCN University of Science and Technology across four designated departments. A total of 120 students enrolled in the Fall 2025 semester participated in the survey. Data collection was executed through a stratified random sampling procedure. The results indicated that students devoted considerable time to utilizing ICT for educational purposes and expressed favorable attitudes toward its application in learning. They acknowledged that ICT significantly contributes to the refinement of their academic abilities; however, they also encountered numerous impediments in classroom usage, such as insufficient training opportunities, technical malfunctions, inadequate user assistance, elevated cost of technological tools, unreliable internet connectivity or infrastructural deficits, concerns over privacy and data protection, and restricted campus internet access. Ultimately, the study proposes several recommendations for higher education administrators and policymakers to facilitate the effective adoption and expansion of ICT in the years ahead. Furthermore, Respondents expected the campus to be able to supply each classroom with suitable equipment and ICT connectivity to enhance the learning process.